Observed Sprite Streamer Growth Rates - H. C. Stenbaek‐Nielsen; M. G. McHarg; N. Y. Liu (Geophysical Research Letters)
Abstract Sprites have been recorded at ∼100,000 frames per second. One hundred and sixty five essentially vertically propagating streamers, 110 downward and 55 upward, have been selected for analysis. The initial velocity increase is exponential as predicted by theory. Growth rates could be determined for 76 downward and 46 upward propagating streamers, and, in individual streamers, they are independent of altitude. The average growth rate increases from 1.6 103 in C‐sprites, to 2.6 103 in carrots, to 8.4 103/s in jellyfish sprites. With a streamer model the driving electric field can be derived. Evaluating the field at 70 km altitude, we find fields of 98 (0.45 Ek), 121 (0.56 Ek), and 188 (0.87 Ek) V/m for the 3 sprite types, indicating that jellyfish sprites are the most energetic. High‐speed imaging can provide streamer growth rates and combined with a streamer model, the electric fields associated with various sprite features can be investigated.